Learning Innovations in Coastal Areas Through Augmented Reality and Gamification - Arianto, Arianto; Hudaibah, Fadlia Dwi; Nurhalifah, Nurhalifah; Qippiah , Mariatul; Bantun, Suharsono (Digital Innovation, 2024)
This research investigates the development of an augmented reality (AR) application with gamification elements to enhance natural science learning in coastal areas. Validation by media and content experts, along with trials conducted among students, showed high feasibility and strong appeal of the application. Functionality tests, including marker detection range, demonstrated the application's capability to operate effectively in diverse coastal environments. The study highlights the successful integration of AR and gamification as a tool to improve engagement and understanding of natural science concepts in under-resourced coastal schools. This application holds great potential for enhancing the quality of education in coastal areas by offering an interactive and immersive learning experience. Further research is recommended to refine the application and assess its long-term impact on student comprehension and educational outcomes in various coastal communities. This study represents a significant step forward in using innovative AR technology to support learning in coastal regions.